Improving English Language Skills in Small Business Management in Kungkung - I Nyoman Muliana; I Gusti Ayu Agung Dian Susanthi; Mirsa Umiyati (Linguistic Community Services Journal, 2025)
The Community Service Program titled "Improving English Proficiency and Promoting Local Cultural Appreciation in Gelgel Village" seeks to address two significant challenges faced by local artisans in Gelgel Village, Klungkung. The first challenge is the limited English language proficiency among the artisans, while the second concerns the growing influence of foreign cultures, brought by both international and domestic tourists, on the younger generation. To enhance English proficiency, the training focuses on "English Functions," an essential aspect of communication with tourists. The Communicative Language Teaching (CLT) method is employed in the training, as it has proven effective in language acquisition. This method emphasizes learner-centered activities, which help increase motivation and engagement, while prioritizing functional communication over the explicit teaching of grammar rules. Furthermore, efforts to preserve local culture are integrated into the program, aiming to raise awareness among artisans about the importance of safeguarding and promoting their cultural heritage. Key topics include understanding local culture, recognizing cultural threats, attitudes toward foreign influences, and strategies for fostering respect and preservation of local traditions. The expected outcomes of this program include a journal article published nationally with an ISSN, media coverage, enhanced competitiveness, the application of scientific and technological advancements, and overall improvements in community values